Effects of Passiflora foetida on the Number of Purkinje Cells in the Cerebellum of Albino Rats - Susilowati, Rina Priastini; Hartono, Budiman (Jurnal Biodjati, 2022)
Â Permot (Passiflora foetida) is one type of plant that has been used as a mosquito coil. Besides being effective at killing Aedes aegypti mosquitoes, mosquito coils made from permot leaf extract are also effective at killing German cockroaches and house flies. Until now there have been no reports stating the side effects of using permot leaf extract in humans.Â This study was designed to demonstrate the harmful side effects of inhalation of smoked mosquito coils made from permot leaf extract on the cerebellar cortex of adult male rats. Thirty-five adult male rats were used in this study. Rats were divided into 7 groups, namely group 1 as a negative control (without exposure), group 2 as a positive control (transfluthrin exposure 3000 ppm), groups 3 to 7 were treatment groups of permot leaf extract with graded doses (500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, and 4000 ppm), and was treatedÂ for 12 weeks. All rats were sacrificed in a timely manner and cerebellar specimens were taken, prepared and observed using a light microscope. Previously, rats were weighed periodically to determine the effect of toxicity. The results showed that exposure to mosquito coil smoke made from 3000 ppm Transflutrin and 4000 ppm permot leaf extract caused weight loss in rats. Likewise on the weight of the rat cerebellum. The effect ofÂ decreasing the number of Purkinje cells also occurred in the group exposedÂ to mosquito coils made from Transflutrin 3000 ppm and permot leaf extract 4000 ppm. Therefore, the safe and effective dose of mosquito coils made from permot leaves is less than 4000 ppm, because exposure to doses of more than 4000 ppm can cause degenerative changes in the cerebellar cortex.